Immunization Coverage Evaluation for the Period of years 2012-2016 in Korce-Albania - Eftiola Pojani; Irsida Mehmeti; Silvi Bozo (European Scientific Journal, ESJ, 2020)
Objective: The objective of this study was to evaluate vaccination coverage retrospectively from birth to 14 year-old children for the period of years 2012-2016, considering also some factors that influence vaccine uptake. Methods: Immunization coverage is the proportion of the number of children vaccinated and those scheduled for vaccination. In this study, this value was calculated referring to the national immunization schedule against diphtheria, tetanus, pertussis, Hepatitis B, mumps, rubella and measles for the district of Korça. Results: Vaccine coverage levels referring to this district for MMR vaccine resulted to be 97.4% and for Hepatitis B vaccine resulted to be always above 98%. As for the third dose of the DTP-HepB-Hib vaccine, the average value was found to be 96%. Conclusion: The 2015-2016 period showed an increase in vaccine coverage values for the DTP vaccine. Also, during this period there was a noticeable drop in the coverage levels for the third booster dose of the penta-valent vaccine (DTP-Hep.B-Hib). Vaccine coverage values analyzed for the year 2016 showed a non-optimal continuity regarding to the fourth booster dose of TT/ Td vaccine.